Avaliação da degradação do óleo diesel por cepas bacterianas isoladas da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The use of oil and its derivatives has enabled technological advances in much of the world, benefiting the economy, industry and society as well. However, all this impact caused direct consequences to the environment and to humanity itself. Pollution caused by oil, oil residues in aquatic and terrestrial environments and the deleterious effects on live animals are some negative factors on environment caused by the excess use of oil and its respective damages. The continuous search for solutions to this problem shows that bioremediation is a viable and promising alternative, where living organisms promote the degradation of toxic compounds in the environment, and many studies in this area have contributed to elucidate the mechanism related to bioremediation by microorganisms. In this work, strains of Burkholderia arboris, Bacillus cereus, Bacillus sp., Burkholderia sp. and Moraxella sp. isolated from consortium were tested to identify characteristics aduring bioremediation of diesel oil. The strains B. arboris and Burkholderia sp. were able to emulsify hexane, xylene and diesel, while Moraxella sp. emulsified only xylene. These strains also adhere to hexane and xylene, but only Moraxella sp. had evidence of biosurfactant production. All strains formed biofilm, and B. arboris, Burkholderia sp. and Moraxella sp. were more resistant to antibiotics than B. cereus and Bacillus sp. Burkholderia arboris, Burkholderia sp. and Moraxella sp. presented toxicity for germination of Lactuca sativa seeds. Results described here contribute to knowledge for proposition of a diesel degrader consortium.
Keywords: Diesel - Biodegradação; Cepas bacterianas; Biorremediação; Xenobióticos; Biofilme; CIÊNCIAS BIOLÓGICAS; Cepas bacterianas; Degradação do diesel; Biorremediação; Xenobióticos